The Effect Of Competitive Advantage, Digital Marketing On Supply Chain Management On Tourism Business Performance In Indonesia - Warti Ratnasari; Hwihanus Hwihanus; Muhammad Bayu; Darmono Darmono (Cita konsultindo, 2023)
The Indonesian tourism industry, which contributes significantly to the national economy and people's welfare, has experienced a decline in performance in recent years. Although it still shows growth compared to other countries, its performance is lower compared to the last two years. This decline was largely attributed to the impact of the Covid-19 pandemic which disrupted the global economy. The consequences of this decline in performance have a negative impact on the benefits this industry generates for Indonesian society. Therefore, appropriate strategies and techniques are needed to improve the performance of the tourism industry and restore its benefits for the people and economy of Indonesia. The purpose of this research is to examine the effects of competitive advantage and digital marketing on tourism business performance. The indirect effects of supply chain management (SCM) are also considered in this study. This study used a quantitative research approach and data collection was carried out through a survey instrument.